2002
DOI: 10.1002/path.1191
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase as a prognostic marker in breast cancer: high‐throughput tissue microarray analysis of hTERT and hTR

Abstract: Telomerase activity (TA) has been shown to correlate with poor clinical outcome in various tumour entities, indicating that tumours expressing this enzyme may be more aggressive and that TA may be a useful prognostic marker. For breast cancer, however, TA is a controversial prognostic marker; whereas some studies suggest an association between TA and disease outcome, others do not find this association. This study used tissue microarrays (breast carcinoma prognosis arrays) containing 611 samples (each 0.6 mm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
3
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 40 publications
(59 reference statements)
5
59
3
2
Order By: Relevance
“…2,[7][8][9][10][11][12][13] Even though a few studies have used tissue microarray to analyze ovarian carcinoma, 14,15 uncertainty has remained as to whether this technique is useful in such heterogeneous tumors. 16,17 Most validation studies have found that analysis of three 0.6-mm cores produces higher concordance rates than use of one core and that use of three cores also reduces the problems of higher case loss that is seen with two cores.…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13] Even though a few studies have used tissue microarray to analyze ovarian carcinoma, 14,15 uncertainty has remained as to whether this technique is useful in such heterogeneous tumors. 16,17 Most validation studies have found that analysis of three 0.6-mm cores produces higher concordance rates than use of one core and that use of three cores also reduces the problems of higher case loss that is seen with two cores.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have used TMA to validate promising results from diagnostic and prognostic biomarker discovery studies. Examples of validation of prognostic biomarkers include an association of elevated expression of COX2 [28], telomerase [29], Ep-CAM/TACSTD1 [30], and EPIL [31] with unfavorable outcome. Proteins associated with a favorable clinical outcome include PHLDA1 [32], and BCL2 [33].…”
Section: Proteomic Profiling Of Human Tissues and Fluidsmentioning
confidence: 99%
“…This prompted us in the present study to subject the same frozen tissues in which we had demonstrated telomerase activity by PCR-ELISA [TRAP-protocol, Kim et al (16)] to an immunohistochemical investigation to find out specifically which cells express the catalytic protein subunit of telomerase, human telomerase reverse transcriptase (hTERT). When we started, the only immunohistochemical hTERT results which had been published related to paraffin sections or cells embedded in paraffin (17)(18)(19)(20)(21)(22). The first challenge was therefore to determine which commercially available antibodies and which method would yield the best nuclear presentation of hTERT in frozen sections.…”
Section: Introductionmentioning
confidence: 99%